Effects of Soil Residues of Sulfosulfuron and Mesosulfuron Methyl + Iodosulfuron Methyl Sodium on Sunflower Varieties - Ahmet Serim; Salih Maden (Journal of Agricultural Sciences)
Using field assays, we studied how the residues of sulfosulfuron and mesosulfuron methyl + iodosulfuron methyl sodium (ME+IMS) applied at two spraying times and three application rates affected two sunflower varieties seeded 12 months after treatment (MAT) in Central Anatolian Region, Turkey. Specifically, we studied their effects on the shoot length, seed yield, and yield components, including plant length, head diameter (HD), and 1000-seed weight. Sunflower yield was found to be the most sensitive biological parameter to the herbicidal residue in the soil, while the 1000-seed weight was the least sensitive. Sulfosulfuron previously applied to winter wheat at two sites greatly reduced subsequent sunflower yield depending on application time, rate, and sunflower variety. At site 1, all sunflower seedlings planted in several plots that were treated with doubled rates of sulfosulfuron died. Similar to the effects of sulfosulfuron residue, ME+IMS previously applied to winter wheat also greatly reduced sunflower yield. Generally, the sunflower yields decreased as the dose of the chosen herbicide increased at both sites. More herbicide molecules were leached or degraded by a variety of pathways when sulfosulfuron and ME+IMS were applied early. The responses of sunflower cultivars to residues of sulfosulfuron and ME+IMS were very similar. Sulfosulfuron residue was more phytotoxic to the sunflower varieties than was ME+IMS at the both sites.